A method for preparing a low thermal expansion coefficient aluminum-clad ceramic lining
By forming an aluminum diamond composite layer and a nickel surface layer on the ceramic lining plate, the problem of mismatch between the thermal expansion coefficient of the ceramic lining plate and the chip is solved, the thermal conductivity and reliability are improved, and it is suitable for high-voltage and high-power power devices.
Patent Information
- Application Number
- CN202410842395.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-06-27
AI Technical Summary
In high-voltage and high-power power devices, existing ceramic lining plates have reliability problems such as loose solder joints and interface fracture due to mismatched thermal expansion coefficients. At the same time, the metal layer with increased thickness increases costs and does not conform to the trend of miniaturization and multifunctionalization.
The diamond is metalized by vacuum microevaporation plating process to form metallized diamond micro powder, and mixed with pure aluminum powder to form an aluminum diamond composite layer through cold spraying process. Combined with the surface nickel plating layer, a low thermal expansion coefficient of aluminum-covered ceramic lining plate was prepared.
The thermal expansion coefficient matching the ceramic lining plate and the chip is realized, which alleviates the stress problems caused by the difference in the thermal expansion coefficient, and improves the thermal conductivity of the ceramic lining plate, solving a series of reliability problems caused by thermal stress.
Smart Images

Figure CN118835200B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor technology, in particular to a method for preparing an aluminum-clad ceramic liner with a low thermal expansion coefficient. Background Art
[0002] With the rapid development of domestic new energy vehicle super-fast charging stations, smart grids, and high-voltage photovoltaic and wind power fields, the demand for high voltage, high power density, and strong heat dissipation of power devices has become more urgent. For power electronic devices, their ceramic linings should have high thermal conductivity, insulation, and heat resistance, as well as high strength and a thermal expansion coefficient that matches the chip. However, as the range of voltage and current that power devices are subjected to becomes larger and larger, the probability of device failure is also becoming greater and greater. The main reason is that heat continues to accumulate inside power electronic components, causing the chip junction temperature to gradually increase, and generating thermal stress, which leads to a series of reliability problems such as reduced life and color temperature changes. Although the problem of thermal stress on the chip can be alleviated by increasing the thickness of the metal layer of the ceramic lining, as the thickness increases, the thermal expansion coefficient of the chip and the ceramic lining is not matched. The mismatch of thermal expansion coefficients causes the internal chips and ceramic linings of power devices to shrink or expand to varying degrees as the temperature changes when the power devices are working, which will generate internal stress on the solder joints or interfaces. In this case, if the quality of the solder joints or interfaces is poor, problems such as loose solder joints and interface fractures are likely to occur. In addition, as the thickness increases, the cost increases and it does not conform to the development trend of miniaturization and multi-functionality of power devices.
[0003] In order to overcome the defects of the prior art, the present invention provides a method for preparing an aluminum-clad ceramic liner with a low thermal expansion coefficient. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing an aluminum-clad ceramic liner with a low thermal expansion coefficient to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A low thermal expansion coefficient aluminum-clad ceramic lining plate comprises a double-sided aluminum-clad ceramic lining plate, both sides of the double-sided aluminum-clad ceramic lining plate are provided with an aluminum-diamond composite layer, and the surface of the aluminum-diamond composite layer is plated with a nickel layer.
[0007] More optimally, the nickel layer has a thickness of 2-4 μm; the aluminum diamond composite layer has a thickness of 20-30 μm, and the weight ratio of pure aluminum powder to metallized diamond powder in the aluminum diamond composite layer is 8:(2.0-2.5); the aluminum thickness of the double-sided aluminum-clad ceramic liner is 0.2-0.8 mm.
[0008] A method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner comprises the following steps:
[0009] Step 1: Forming a layer of metallic copper on the surface of diamond micropowder by vacuum micro-evaporation plating process to prepare metallized diamond micropowder;
[0010] Step 2: Mix the metallized diamond powder obtained in step 1 with pure aluminum powder, and process by cold spraying to form an aluminum-diamond composite layer on the double-sided aluminum-coated ceramic liner for standby use;
[0011] Step three: pre-treat the double-sided aluminum-clad ceramic lining plate obtained in step two, and then perform surface nickel plating to obtain a finished product.
[0012] More optimally, in step 1, the particle size of the diamond powder is 10-15 μm; the thickness of the metallic copper is 0.1-0.2 μm.
[0013] More optimally, in step 1, vacuum micro-evaporation coating process: vacuum degree is 2.0×10 -5 -5.0×10 -4 Pa, the deposition temperature is 300-400℃, the deposition rate is 0.1-0.5nm / s, the coating time is 15-40min, and the evaporation rate is 1.0-2.0A / s.
[0014] More optimally, in step 2, the particle size of the pure aluminum powder is 10-15 μm.
[0015] More optimally, in step 2, the cold spray process: the nozzle diameter is 0.5-1.5 mm, the spray gun air pressure is 0.7-1 MPa, the gas flow rate is 100-400 L / min, the powder gas flow velocity is 300-600 m / s, and the powder feeding amount is 5-20 g / min.
[0016] More optimally, in step three, the pretreatment process is alkali washing for 3-5 minutes, acid washing for 90-100 seconds, primary zinc immersion for 40-50 seconds, acid washing for 90-100 seconds, and secondary zinc immersion for 30-40 seconds, and pure water washing is performed after each step is completed.
[0017] Preferably, in step 3, the surface nickel plating is a sodium hypophosphite system chemical nickel plating; the composition of the sodium hypophosphite chemical nickel plating solution is: NiSO 4 7H 2 O is 25-30 g / L, NaH 2 PO 2 ·H 2 O is 25-30g / L, CH 3 COONa is 15-20g / L, Na 3 C 6 H 5O·2H 2 O is 10-20g / L.
[0018] More optimally, in step three, when nickel is plated on the surface, the temperature is 78-85°C, the time is 15-25 minutes, and the stirring method is air stirring.
[0019] Beneficial effects of the present invention:
[0020] The feature of the present invention is that diamond is metallized by a vacuum micro-evaporation plating process to obtain metallized diamond micropowder. The metallized diamond micropowder is mixed with pure aluminum powder and treated by a cold spray process to form an aluminum-diamond composite layer on a double-sided aluminum-coated ceramic liner. The treated double-sided aluminum-coated ceramic liner is first pre-treated and then nickel-plated on the surface to form a structure of surface coating-aluminum-diamond composite layer-double-sided aluminum-coated ceramic liner-aluminum-diamond composite layer-surface coating. The finished product prepared by the present invention uses the aluminum-diamond composite layer as an intermediate layer and has a thermal expansion coefficient that matches the chip, which greatly alleviates the stress problem caused by the difference in thermal expansion coefficients. In addition, the structure improves the thermal conductivity of the aluminum-coated ceramic liner and solves a series of reliability problems caused by thermal stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 It is a structural schematic diagram of the finished product of the present invention;
[0023] Figure 2 This is the surface appearance of Example 1 of the present invention after the hot and cold cycle test;
[0024] Figure 3 This is the surface appearance of Example 2 of the present invention after the hot and cold cycle test;
[0025] Figure 4 This is the surface appearance of comparative example 1 of the present invention after hot and cold cycle testing. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Source of raw materials:
[0028] Spherical pure aluminum powder, content greater than 99.9%.
[0029] Example 1: Step 1: Take 20 g of diamond micropowder with a particle size of 10 μm, and form a layer of metal copper with a thickness of 0.18 μm on the surface of the diamond micropowder through a vacuum microevaporation plating process to prepare metallized diamond micropowder; vacuum microevaporation plating process: the vacuum degree is 3×10 -5 Pa, deposition temperature is 350 °C, deposition rate is 0.2 nm / s, coating time is 15 min, and evaporation rate is 1.5 A / s;
[0030] Step 2: 20g of metallized diamond powder and 80g of spherical pure aluminum powder with a particle size of 12μm are mixed, and a 25μm thick aluminum diamond composite layer is formed on the double-sided aluminum-coated ceramic liner through a cold spraying process; cold spraying process: nozzle diameter is 1mm, spray gun air pressure is 0.7Mpa, gas flow rate is 200L / min, powder gas flow rate is 400m / s, and powder feeding amount is 10g / min; double-sided aluminum-coated ceramic liner, specifications are 139×190×1.0mm, roughness Ra is 1.0μm, and aluminum thickness is 0.4mm;
[0031] Step 3: The double-sided aluminum-clad ceramic lining plate obtained in step 2 is pretreated first, and then surface nickel-plated, with a nickel layer thickness of 3.5 μm, to obtain a finished product; the pretreatment process is alkali washing for 3 minutes, acid washing for 90 seconds, zinc immersion for 40 seconds, acid washing for 90 seconds, and zinc immersion for 30 seconds, and pure water washing is performed after each step is completed; the surface nickel plating is sodium hypophosphite system chemical nickel plating; the composition of the sodium hypophosphite chemical nickel plating solution is: NiSO 4 7H 2 O is 25 g / L, NaH 2 PO 2 ·H 2 O is 25 g / L, CH 3 COONa is 15g / L, Na 3 C 6 H 5 O·2H 2 O is 10g / L; when nickel is plated on the surface, the temperature is 83℃, the time is 15min, and the stirring method is air stirring.
[0032] Example 2: Step 1: Take 20 g of diamond micropowder with a particle size of 10 μm, and form a layer of metal copper with a thickness of 0.2 μm on the surface of the diamond micropowder through a vacuum microevaporation plating process to prepare metallized diamond micropowder; vacuum microevaporation plating process: the vacuum degree is 4.5×10 -5 Pa, deposition temperature is 345 °C, deposition rate is 0.25 nm / s, coating time is 15 min, and evaporation rate is 1.2 A / s;
[0033] Step 2: 20g of metallized diamond powder and 80g of spherical pure aluminum powder with a particle size of 13μm are mixed, and treated by cold spraying process to form an aluminum diamond composite layer with a thickness of 28μm on the double-sided aluminum-coated ceramic liner; cold spraying process: nozzle diameter is 1.2mm, spray gun air pressure is 0.9Mpa, gas flow rate is 235L / min, powder gas flow rate is 405m / s, and powder feeding amount is 15g / min; double-sided aluminum-coated ceramic liner, specifications are 139×190×1.2mm, roughness Ra is 1.0μm, and aluminum thickness is 0.2mm;
[0034] Step 3: The double-sided aluminum-clad ceramic lining plate obtained in step 2 is pretreated first, and then surface nickel-plated, with a nickel layer thickness of 3.2 μm, to obtain a finished product; the pretreatment process is alkali washing for 3 minutes, acid washing for 90 seconds, zinc immersion for 40 seconds, acid washing for 90 seconds, and zinc immersion for 30 seconds, and pure water washing is performed after each step is completed; the surface nickel plating is sodium hypophosphite system chemical nickel plating; the composition of the sodium hypophosphite chemical nickel plating solution is: NiSO 4 7H 2 O is 25 g / L, NaH 2 PO 2 ·H 2 O is 25g / L, CH 3 COONa is 15g / L, Na 3 C 6 H 5 O·2H 2 O is 10g / L; when nickel is plated on the surface, the temperature is 80℃, the time is 15min, and the stirring method is air stirring.
[0035] Comparative Example 1: The preparation step of the aluminum diamond composite layer is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The double-sided aluminum-coated ceramic liner is pretreated first, and then the surface is nickel-plated, and the thickness of the nickel layer is 3.6 μm to prepare a finished product; the pretreatment process is alkali washing for 3 minutes, acid washing for 90 seconds, zinc immersion for 40 seconds, acid washing for 90 seconds, and zinc immersion for 30 seconds, and pure water washing is performed after each step is completed; the surface nickel plating is sodium hypophosphite system chemical nickel plating; the composition of the sodium hypophosphite chemical nickel plating solution is: NiSO 4 7H 2 O is 25 g / L, NaH 2 PO 2 ·H 2 O is 25 g / L, CH 3 COONa is 15g / L, Na 3 C 6 H 5 O·2H 2O is 10g / L; when nickel is plated on the surface, the temperature is 82℃, the time is 15min, and the stirring method is air stirring; the double-sided aluminum-coated ceramic liner has a specification of 139×190×1.0mm, a roughness Ra of 1.0μm, and an aluminum thickness of 0.4mm.
[0036] Detection test:
[0037] Roughness test: The finished product prepared by the present invention is used as a sample, and the sample is subjected to a roughness test using a MarSurfM 310 portable roughness measuring instrument. Ten different areas of each sample are measured to reduce errors, and the average value is taken as the final result.
[0038] Hot and cold cycle performance test: The finished product prepared in the Ming Dynasty was used as a sample, and the hot and cold cycle test of zinc dipping was carried out in a TSE-12-A high and low temperature cycle test chamber. Parameter setting: Cycle temperature: -40℃~125℃, test standard is GB / T 2423.22-2012 Environmental testing Part 2: Test method Test N: Temperature change. Each sample was cycled 1500 times.
[0039] Table 1 is a comparison of roughness values before and after thermal cycling of Example 1 of the present invention;
[0040] Table 2 is a comparison of roughness values before and after thermal cycling of Example 2 of the present invention;
[0041] Table 3 is a comparison of roughness values before and after thermal cycling of Comparative Example 1 of the present invention.
[0042] Table 1
[0043] Serial number Roughness before test Roughness after test 1 0.327 0.771 2 0.352 0.795 3 0.294 0.825 4 0.335 0.857 5 0.311 0.863 6 0.374 0.783 7 0.356 0.811 8 0.343 0.792 9 0.372 0.755 10 0.323 0.804 average value 0.339 0.806
[0044] Table 2
[0045] Serial number Roughness before test Roughness after test 1 0.317 0.752 2 0.404 0.741 3 0.347 0.730 4 0.329 0.742 5 0.358 0.801 6 0.375 0.811 7 0.366 0.795 8 0.345 0.742 9 0.381 0.758 10 0.369 0.764 average value 0.359 0.764
[0046] Table 3
[0047]
[0048]
[0049] Conclusion: A hot and cold cycle test was used for comparative experiments. The cycle test was 1500 times. The surface roughness test was carried out before the test and after the test.
[0050] By comparison, it can be found that there is no obvious change in the surface of Example 1 and Example 2 after 1500 hot and cold cycle tests, while water ripples appear on the surface of Comparative Example 1 after 1500 hot and cold cycle tests. Secondly, through Table 1, Table 2 and Table 3, it can be reflected that the roughness change of Example 1 and Example 2 before and after the hot and cold cycle test is small, while the roughness change of Comparative Example 1 before and after the hot and cold cycle is large, and the roughness increases sharply after the hot and cold cycle test.
[0051] Therefore, the present invention designs a structure of surface coating-aluminum diamond composite layer-double-sided aluminum-clad ceramic lining plate-aluminum diamond composite layer-surface coating layer, so that the aluminum-clad ceramic lining plate has a thermal expansion coefficient that matches the chip, which greatly alleviates the stress problem caused by the difference in thermal expansion coefficient. In addition, this structure improves the thermal conductivity of the aluminum-clad ceramic lining plate and solves a series of reliability problems caused by thermal stress.
[0052] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low thermal expansion coefficient aluminum-clad ceramic liner, characterized in that: It comprises a double-sided aluminum-clad ceramic lining plate, wherein aluminum-diamond composite layers are arranged on both sides of the double-sided aluminum-clad ceramic lining plate, and a nickel layer is plated on the surface of the aluminum-diamond composite layer; the nickel layer has a thickness of 2-4μm; the aluminum-diamond composite layer has a thickness of 20-30μm, and the weight ratio of pure aluminum powder to metallized diamond micropowder in the aluminum-diamond composite layer is 8:(2.0-2.5); the aluminum thickness of the double-sided aluminum-clad ceramic lining plate is 0.2-0.8mm.
2. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 1, characterized in that: The following steps are involved: Step 1: Forming a layer of metallic copper on the surface of diamond micropowder by vacuum micro-evaporation plating process to prepare metallized diamond micropowder; Step 2: Mix the metallized diamond powder obtained in step 1 with pure aluminum powder, and process by cold spraying to form an aluminum-diamond composite layer on the double-sided aluminum-coated ceramic liner for standby use; Step three: pre-treat the double-sided aluminum-clad ceramic lining plate obtained in step two, and then perform surface nickel plating to obtain a finished product.
3. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step 1, the particle size of the diamond powder is 10-15 μm; the thickness of the metal copper is 0.1-0.2 μm.
4. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step 2, the particle size of the pure aluminum powder is 10-15 μm.
5. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step 2, cold spray process: nozzle diameter is 0.5-1.5mm, spray gun air pressure is 0.7-1Mpa, gas flow rate is 100-400L / min, powder air flow velocity is 300-600m / s, and powder feeding amount is 5-20g / min.
6. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step three, the pretreatment process is alkali washing for 3-5 minutes, acid washing for 90-100 seconds, primary zinc immersion for 40-50 seconds, acid washing for 90-100 seconds, and secondary zinc immersion for 30-40 seconds, and pure water washing is performed after each step is completed.
7. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step three, the surface nickel plating is sodium hypophosphite system chemical nickel plating; the composition of the sodium hypophosphite chemical nickel plating solution is: NiSO4·7H2O is 25-30g / L, NaH2PO2·H2O is 25-30g / L, CH3COONa is 15-20g / L, and Na3C6H5O·2H2O is 10-20g / L.
8. The method for preparing a low thermal expansion coefficient aluminum-clad ceramic liner according to claim 2, characterized in that: In step 3, when the surface is nickel-plated, the temperature is 78-85° C., the time is 15-25 min, and the stirring method is air stirring.
Citation Information
Patent Citations
Preparation method of aluminum nitride aluminum-coated ceramic lining plate
CN113213972A
Method for improving heat-resistant cycle reliability of aluminum nitride aluminum-coated packaging lining plate
CN115410925A